National economic identity and capital mobility: State-business relations in Latin America (2012)
Why has capital account liberalization been a durable policy in some countries, but not in others? The book uses the contrast between the path pursued by Peru and Colombia regarding capital account policy during the last twenty years in order to identify two critical factors to account for this puzzle. First, changes in domestic informal institutions are a necessary element of sustainable capital account policy choices. Second, sustainable capital account liberalization presupposes that business-government relations privilege the interests of economic sectors that depend on the unfettered flow of international capital and are largely unaffected by exchange-rate volatility over the interests of exporters of non-traditional goods worried about exchange-rate appreciation in the context of capital account openness.